Comparative risk assessment modeling of cardiovascular and all-cause burden attributable to sitting time and physical inactivity: evidence from Argentina - García-Witulski, Christian (2024)
Fil: García Witulski, Christian M. Pontificia Universidad Católica Argentina. Facultad de Ciencias Económicas. Centro de Desarrollo Humano Sostenible; Argentina